2017
DOI: 10.1080/13696998.2017.1362412
|View full text |Cite
|
Sign up to set email alerts
|

Incremental economic burden associated with major bleeding among atrial fibrillation patients treated with factor Xa inhibitors

Abstract: Objective: To evaluate healthcare resource use and costs incurred during, as well as following hospitalization for major bleeding (MB), among atrial fibrillation (AF) patients treated with factor Xa inhibitors Methods: Patients with an AF diagnosis and MB hospitalization (index event) were identified from the MarketScan Commercial and Medicare databases (January 1, 2011-December 31, 2014. Patients were required to have 1 prescription for rivaroxaban or apixaban within 3 months prior to MB hospitalization. AF p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
(27 reference statements)
1
22
0
1
Order By: Relevance
“…[1][2][3][4][5] In one real-world study of patients with AF who were treated with oral factor Xa inhibitors, those who were hospitalized with a major bleed of any type were found to have mean hospital stays exceeding 5 days and inpatient mortality rates of approximately 3%, though mortality risk was notably higher for patients with intracranial hemorrhage (ICH) (approximately 14%). 4 There is a scarcity of nationally representative data describing the incidence and burden-of-illness of bleeding-related hospitalizations in AF patients, both overall and by bleed subtype. The availability of contemporary data on this topic would allow clinicians and other decision-makers to better understand the absolute and relative risks of detrimental outcomes across various bleeding-related hospitalization types.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In one real-world study of patients with AF who were treated with oral factor Xa inhibitors, those who were hospitalized with a major bleed of any type were found to have mean hospital stays exceeding 5 days and inpatient mortality rates of approximately 3%, though mortality risk was notably higher for patients with intracranial hemorrhage (ICH) (approximately 14%). 4 There is a scarcity of nationally representative data describing the incidence and burden-of-illness of bleeding-related hospitalizations in AF patients, both overall and by bleed subtype. The availability of contemporary data on this topic would allow clinicians and other decision-makers to better understand the absolute and relative risks of detrimental outcomes across various bleeding-related hospitalization types.…”
Section: Introductionmentioning
confidence: 99%
“…The per event readmission costs for MB and stroke among NVAF patients have not been well documented in the published literature. However, a database claims study of patients with an AF diagnosis and a hospitalization for an MB event reported a mean hospital cost of $28,509 per patient (2014 USD) 26 . Costs for hospital readmissions of NVAF patients are substantial and possibly increasing.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the MarketScan databases, approximately 2.9 million people in the U.S. were treated with FXa inhibitors in 2015 [31]. There are currently > 80,000 annual U.S. FXa inhibitor-associated, ISTH-defined major bleeding events [8]. Reversal agents may only be required in a subset, perhaps a third to a half (see Note S1 for explanation), but that number is anticipated to grow, and data presented here contradicts the notion that FXa inhibitor-associated bleeding is mild and reversal agents serve a psychological more than a medical need [32].…”
Section: Discussionmentioning
confidence: 99%
“…These drugs are easier to manage than VKAs as they do not require routine monitoring of the international normalized ratio and are associated with less intracranial hemorrhage (ICH) [25]. Meta-analyses suggest superiority in both safety and efficacy of the newer drugs over VKAs; [6,7] however, serious bleeding still occurs, with an estimated 80,000 cases of major hemorrhage in the U.S. annually on FXa inhibitors alone [8]. …”
Section: Introductionmentioning
confidence: 99%